SUSTAINABLE FACTORS IN THE HUMAN ASSETS OF DANA HOTEL AS A HERITAGE HOTEL IN SOLO, INDONESIA - Wahyuniwati Wahyudi; Endo W. Kartika; Sia Tjun Han (Jurnal Manajemen dan Kewirausahaan, 2018)
This research aims to study what sustainable factors of Dana Hotel in the human assets; and also find out what the status of Dana Hotel, using VRIN analysis (Value, Rarity, Imperfect Imitability, and Non-Substitutability) from Natural Language Data of observation and in-depth interviews in a descriptive qualitative study. In results, in order to achieve sustainability, Dana Hotel has valuable, rare, imperfectly imitable, and non-substitutable factors in the human assets. As the human assets are valuable, rare, imperfectly imitable, and non-substitutable, the status of Dana Hotel is sustainable in the context of human resources. It is concluded that following the success of Dana Hotel, organizations that have those factors or even more, tend to have big opportunities to survive.